Do Business Professionals Exhibit Racial Bias in Strategic Marketing Decisions? - Jacob, Jorge; Vieites, Yan (Journal of Marketing, 2026)
This research investigates whether business professionals, on average, exhibit racial bias in strategic marketing decisions involving Black consumers. Across nine studies and four replications with current and aspiring business professionals from the United States, France, and Brazil, the authors find evidence that commonly held lay theories linking Blackness with economic hardship are associated with racialized interpretations of income. Specifically, professionals tend to perceive Black consumers as lower income than equally earning White consumers. These perceptions, in turn, are associated with consumption-specific stereotypes that characterize Black consumers as more price sensitive and less attuned to quality, innovation, and customization. As a result, professionals are less likely to prioritize predominantly Black consumer markets in core marketing decisions, such as market entry and product portfolio selection, even in contexts where these markets offer greater objective economic potential (i.e., higher individual and aggregate income). Importantly, the findings show that both diversity training and deliberation-based interventions reduce the likelihood of such biases. The authors discuss implications for marketing practice and marketplace equity.